Amino and fatty acids composition of olive stones for the discrimination of 'Olea europaea' subsp. 'europaea' varieties - Hannachi, Hédia; Benabderrahim, Mohamed Ali; Elfalleh, Walid; Wang, Rongchun; Ying, Ma (Mediterranean Botany, 2020)
Few studies have reported the relationship between wild (Olea europaea L. subsp. europaea var. sylvestris) and cultivated (Olea europaea L. subsp. europaea var. europaea) olive trees by using diverse markers. Herein, the amino and fatty acids composition of stones from wild and cultivated olives were assessed respectively using amino acids analyzer and gas chromatography coupled with mass spectrometry. Stones of 24 Tunisian olive samples including twelve cultivated trees and twelve wild trees were obtained from olives harvested at ripe stage. Results showed that 17 amino acids (with eight essential amino acids) and 15 fatty acids (eight saturated and seven unsaturated) were detected in the both olive taxa. Statistically, significant differences among wild and cultivated stones were observed for amino and fatty acids contents. Based on the major fatty acids and the essential amino acids, multivariate analyses classified olive varieties into three groups showing a close relationship between some wild and cultivated olive trees. Results were useful to distinguish some interest wild olive genotypes having stones richer in essential amino acids and monounsaturated fatty acids. Wild olive trees would constitute a genetic pool of interest criteria. These data would be used as complementary tool to morphological traits and molecular markers studies providing a relationship between the cultivated and wild olive trees.